1961
DOI: 10.1002/jctb.5010110305
|View full text |Cite
|
Sign up to set email alerts
|

Separation of thorium from uranium and rare‐earth elements by solvent extraction with tri ‐ n ‐ butyl phosphate ‐ xylene

Abstract: A study is made of three processes for the separation of thorium from uranium and rare‐earth elements in crude thorium nitrate solutions prepared by breakdown of monazite sand. Uranium may be separated from thorium and rare‐earth elements in a preliminary extraction with 5% or 40% v/v tri‐n‐butyl phosphate (TBP) in xylene and the thorium separated from the rare‐earth elements in a subsequent extraction with 40% v/v TBP in xylene. Alternatively thorium and uranium may be extracted simultaneously from the soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The extraction of uranium by TBP is much stronger than that of thorium and REEs. Menzies and Rigby used 5% (v/v) TBP in xylene to extract uranium and separate it from thorium and REEs from the nitrate solution . The separation of thorium, uranium, and REEs was investigated in a series of acidic solutions with Cyanex 923 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction of uranium by TBP is much stronger than that of thorium and REEs. Menzies and Rigby used 5% (v/v) TBP in xylene to extract uranium and separate it from thorium and REEs from the nitrate solution . The separation of thorium, uranium, and REEs was investigated in a series of acidic solutions with Cyanex 923 .…”
Section: Introductionmentioning
confidence: 99%
“…Menzies and Rigby used 5% (v/v) TBP in xylene to extract uranium and separate it from thorium and REEs from the nitrate solution. 48 The separation of thorium, uranium, and REEs was investigated in a series of acidic solutions with Cyanex 923. 49 It has been reported that Cyanex 272 can strongly extract thorium and uranium even in strong HNO 3 solutions, up to 4 M. 50 Uranium and thorium can also be extracted by TBP from the HCl solution.…”
Section: Introductionmentioning
confidence: 99%